The extermination of ethical decorum within local government in South Africa : is it a total fiasco? - Mashilo, M. T.; Selelo, M. E. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
This paper investigates the death of ethical integrity within the local government. In that, the purpose of the paper is to vigorously critique the weakening ethical behaviour in local government. The paper derives its thesis statement following the dilution on the effectiveness of local government to render services to its constituencies and the recurring monstrous misbehaviour of those occupying public offices. Meanwhile, at the current juncture, South Africa is sinking deep into the pool of tripartite grief of socio-economic aspects. What is of a concern is that the "ethics" which are part of leadership are overlooked because of self-ambition of public servants. Notably, the public office bearers continue to engage in evil activities that have a direct impact on the daily functioning of local government. A worrying factor is that tender-awarding processes and procurement are at the realm of the people whom in political line say, "They know processes". Such processes are the ones concealing corruption. Failure to adopt ethical integrity reveals a dysfunctional and moribund of local government. Pragmatically, the state of local government in the country is in crisis, wherein people persist to languish in dreadful conditions of life and remain destitute in an epoch of democracy. These elements are as the repercussions of the death of ethics in the municipalities. The paper is informed by the recent corruption and maladministration scandals transpiring in the different municipalities to empirically strengthen its argument. The paper uses literature-based methodology to critique in detail the extent in which the death of ethics affects the functioning of local government and service delivery. The paper further recommends mechanisms to strengthen internal governance to ensure the adherence to ethical fundamentals in local government.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Democracy; Ethics; Local government; Public servants; Service delivery; Local government--South Africa; Business ethics